Reform Paths and Institutional Resilience - Clemens Buchen (ZBW - Leibniz Information Centre for Economics, 2021)
Broadly speaking, institutional reformers decide about the sequencing of types of reforms, either addressing institutional quality or macroeconomic stability. This paper develops a dynamic population game, in which agents play a simple anonymous-exchange game of cooperating or defecting. Agents switch to the strategy with higher expected payoff. Reformers can affect the payoff structure of the stage game in order to maximize the number of cooperators in the population by either enacting legal reform (rule of law) or focusing on the macro outlook of the economy facilitating cooperation. Reform is cumulative and starts from initial conditions. Reform effort per period of time is capped. On the basis of the theoretical model the paper makes predictions under which conditions which types of reforms should be enacted first and under which conditions reform will not be successful. In addition, the notion of institutional resilience is introduced as a minimum threshold of legal quality, which allows the population to better withstand exogenous shocks.
Keywords: C61; C72; C73; D78; P16; 330